Quality Diets for Better Health (QDBH) - International Potato Center (2018)
Locally adapted Orange-Fleshed Sweetpotato varieties, nutrition education and infant feeding tools are tested to address malnutrition in Southern Nations, Nationalities and Peoples Region (SNNPR), Ethiopia. This year baseline studies and formative research were completed and the first 26 Healthy Living Clubs set up and activities implemented with 1,117 participants.